2013
DOI: 10.1124/jpet.112.201855
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Chemotaxis Caused by Chronic Obstructive Pulmonary Disease Alveolar Macrophages: The Role of CXCL8 and the Receptors CXCR1/CXCR2

Abstract: Alveolar macrophages produce neutrophil chemoattractants; this cellular cross-talk contributes to neutrophilic airway inflammation in chronic obstructive pulmonary disease (COPD). We have investigated the chemotaxis cross-talk mechanisms between these cells using COPD alveolar macrophages. Using conditioned media from stimulated COPD alveolar macrophages, we investigated the relative contributions of growthrelated oncogene (CXCL1), interleukin-8 (CXCL8), and regulated on activation normal T cell expressed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 33 publications
3
49
0
1
Order By: Relevance
“…A549 cells, a type II alveolar epithelial cell line, produce IL-8 and monocyte chemotactic protein 1 (MCP-1), which function as chemoattractants for neutrophils, T cells, basophils, and monocytes, in the early stages of M. tuberculosis infection (12,13).…”
mentioning
confidence: 99%
“…A549 cells, a type II alveolar epithelial cell line, produce IL-8 and monocyte chemotactic protein 1 (MCP-1), which function as chemoattractants for neutrophils, T cells, basophils, and monocytes, in the early stages of M. tuberculosis infection (12,13).…”
mentioning
confidence: 99%
“…This has suggested a role for chemokines in mediating neutrophil recruitment and differentiation within inflamed tissue (20). Indeed, the chemokines CXCL8 (formerly known as IL-8) and CCL5 (formerly known as RANTES) are known to be potent activators of neutrophil recruitment (21,22).…”
mentioning
confidence: 99%
“…Previously we have shown that supernatants from COPD lung macrophages induce neutrophil chemotaxis that is CXCL8 dependent, and that corticosteroids have little effect on this macrophage induced neutrophil chemotaxis [26] . Furthermore, we have demonstrated that pulmonary neutrophils express very low levels of GR in both COPD patients and controls [27] .…”
mentioning
confidence: 89%